Analysis of Measles-Mumps-Rubella (MMR) Titers of Recovered COVID-19 Patients - Jeffrey E. Gold (American Society for Microbiology, 2020)
ABSTRACT The measles-mumps-rubella (MMR) vaccine has been theorized to provide protection against coronavirus disease 2019 (COVID-19). Our aim was to determine whether any MMR IgG titers are inversely correlated with severity in recovered COVID-19 patients previously vaccinated with MMR II. We divided 80 subjects into two groups, comparing MMR titers to recent COVID-19 severity levels. The MMR II group consisted of 50 subjects who would primarily have MMR antibodies from the MMR II vaccine, and a comparison group of 30 subjects consisted of those who would primarily have MMR antibodies from sources other than MMR II, including prior measles, mumps, and/or rubella illnesses. There was a significant inverse correlation (rs = −0.71, P < 0.001) between mumps virus titers (mumps titers) and COVID-19 severity within the MMR II group. There were no significant correlations between mumps titers and severity in the comparison group, between mumps titers and age in the MMR II group, or between severity and measles or rubella titers in either group. Within the MMR II group, mumps titers of 134 to 300 arbitrary units (AU)/ml (n = 8) were found only in those who were functionally immune or asymptomatic; all with mild symptoms had mumps titers below 134 AU/ml (n = 17); all with moderate symptoms had mumps titers below 75 AU/ml (n = 11); all who had been hospitalized and had required oxygen had mumps titers below 32 AU/ml (n = 5). Our results demonstrate that there is a significant inverse correlation between mumps titers from MMR II and COVID-19 severity. IMPORTANCE COVID-19 has presented various paradoxes that, if understood better, may provide clues to controlling the pandemic, even before a COVID-19 vaccine is widely available. First, young children are largely spared from severe disease. Second, numerous countries have COVID-19 death rates that are as low as 1% of the death rates of other countries. Third, many people, despite prolonged close contact with someone who is COVID-19 positive, never test positive themselves. Fourth, nearly half of people who test positive for COVID-19 are asymptomatic. Some researchers have theorized that the measles-mumps-rubella (MMR) vaccine may be responsible for these disparities. The significance of our study is that it showed that mumps titers related to the MMR II vaccine are significantly and inversely correlated with the severity of COVID-19-related symptoms, supporting the theorized association between the MMR vaccine and COVID-19 severity.